Osteogenic Differentiation of Mesenchymal Stem Cells via Curcumin-Containing Nanoscaffolds. (19th July 2021) - Khezri, Khadijeh; Maleki Dizaj, Solmaz; Rahbar Saadat, Yalda; Sharifi, Simin; Shahi, Shahriar; Ahmadian, Elham; Eftekhari, Aziz; Dalir Abdolahinia, Elaheh; Lotfipour, Farzaneh
Abstract : The diverse pleiotropic pharmacological effects of curcumin nanoformulations have turned it into an attractive natural compound in different health-related problems. A great body of evidence has shown the impact of curcumin and its nanoformulations on the differentiation of stem cells. The current review highlights cellular and molecular mechanisms connected with the osteogenic differentiation of mesenchymal stem cells (MSCs) in the scaffolds benefiting from the presence of nanocurcumin pointing toward the role of inhibitory or stimulant signal transduction pathways in detail. Moreover, the effects of different concentrations as well as the structural modifications of curcumin on the differentiation of MSCs have been addressed.